Ground-based Analogue Testing: Status of the EDEN ISS Greenhouse System after a Successful Deployment Phase in Antarctica - Schubert, Daniel; Zeidler, Conrad; Vrakking, Vincent; Zabel, Paul (2018)
An important step towards reliable human space exploration scenarios is ground-based testing of essential technologies enabling the presence of humans on extraterrestrial bodies. Here, analogue testing of plant cultivation technologies as an integrated element of bio regenerative life support systems represents a useful undertaking. These ground-based test campaigns result in a better understanding of the necessary technologies, implemented procedures, and, more importantly, unexpected challenges to overcome, making future human surface missions more predictable and plannable. As a European project, the EDEN ISS consortium focused on advancing Controlled Environment Agriculture technologies and adjoining research fields for safe food production in closed-loop space systems such as planetary habitats or transfer vehicles. A dedicated greenhouse system, called Mobile Test Facility, was designed, built and deployed to the German Neumayer III research station in Antarctica. Here, the overwintering crew of 10 people is provided with fresh vegetables during their isolation phase. The presentation provides an overview of the as-built design configuration of the Mobile Test Facility. A detailed overview is given of the assembly integration and test phase that took place at the DLR Institute of Space Systems during the year 2017. Furthermore the main phases of the deployment mission in Antarctica are presented, which took place from December 2017 to February 2018. First observations of the ramp up phase are given and first scientific outcomes are presented.